Open World Program - Building the bridge between USA and countries of Eurasia - Mihajlović, Ivan; Otašević, Milena (Serbian Journal of Management, 2015)
This Editor Note is aiming to promote the efforts of the Open World Program in its mission to enhance understanding and capabilities for cooperation between the United States and the countries of Eurasia by developing a network of leaders in the region who have gained significant, firsthand exposure to America’s democratic, accountable government and its free-market system (www.openworld.gov). The text written in this article is based on the facts about the program, obtained from Mrs. Milena Otašević, former Program Coordinator of the Open World Program in Serbia and personal experience of Ivan Mihajlović, Editor in Chief of SJM, who had opportunity to be included as participant in this program during the year 2014. The goal of this text is to give additional acknowledgement for this noble intention of the United States Congress, which is the founding institution of the Program and to familiarize the opportunity to be included in this program initiative to vide SJM audience.